Conventional Medicinal Uses, Phytoconstituents, and Biological Activities of Euphorbia officinarum L.: A Systematic Review - Imane Chamkhi; Mohamed Hnini; Jamal Aurag (Advances in Pharmacological and Pharmaceutical Sciences)
The Moroccan endemic plant Euphorbia officinarum is a traditional medicinal plant, known locally as “Daghmus.” Plants in the genus Euphorbia are well known for the chemical diversity of their diterpenoids and isoprenoid constituents, which perform many activities such as cytotoxic, antimicrobial, and anti-inflammatory activities, as well as different biological properties, that cannot be overlooked. The effect of bioactive compounds (antiviral, antidiabetic, anticancer, and antioxidant). Euphorbia officinarum is an important conventional medicine for the treatment of various conditions, including skin and ophthalmological diseases. It is also used against human pathogens (intestinal parasites). E. officinarum latex is the major part of the plant used for conventional medicine and synthesizing new bioactive compounds. The characterization and isolation of its components are necessary to exploiting and enhancing its therapeutic potential. However, to the best of our knowledge, no review is available to date. In order to have and define a research question, we adopt a strategy by considering the items of the PRISMA checklist. Therefore, this review aims to cover E. officinarum taxonomy, botanical description, distribution, conventional uses, and phytochemical compounds of this plant, including the biological activities of compounds isolated and of these semisynthesized compounds. This article provides a foundation for any further studies from this plant.